Laser Surface Processing and Model Studies - Yilbas, Bekir Sami.; Shuja, Shahzada Zaman; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book introduces model studies associated with laser surface processing such as conduction limited heating, surface re-melting, Marangoni flow and its effects on the temperature field, re-melting of multi-layered surfaces, laser shock processing, and practical applications. The book provides insight into the physical processes involved with laser surface heating and phase change in laser irradiated region. It is written for engineers and researchers working on laser surface engineering.
Conduction Heating of Solid Surfaces -- Laser Melting of Solid Surfaces -- Laser Melting of Two Layer Materials -- Laser Induced Evaporation at the Surface -- Practical Applications of Laser Surface Treatment.
Keywords: Engineering; Structural control (Engineering).; Surfaces (Physics).; Engineering; Operating Procedures, Materials Treatment; Laser Technology, Photonics; Surfaces and Interfaces, Thin Films